Hepatitis C virus testing, liver disease assessment and treatment uptake among people who inject drugs pre‐ and post‐universal access to direct‐acting antiviral treatment in Australia: The LiveRLife study. Issue 3 (6th December 2019) - Bajis, Sahar; Grebely, Jason; Hajarizadeh, Behzad; Applegate, Tanya; Marshall, Alison D.; Ellen Harrod, Mary; Byrne, Jude; Bath, Nicky; Read, Phillip; Edwards, Michael; Gorton, Carla; Hayllar, Jeremy; et al.
Abstract: Gaps in hepatitis C virus (HCV) testing, diagnosis, liver disease assessment and treatment uptake among people who inject drugs (PWID) persist. We aimed to describe the cascade of HCV care among PWID in Australia, prior to and following unrestricted access to direct‐acting antiviral (DAA) treatment. Participants enrolled in an observational cohort study between 2014 and 2018 provided fingerstick whole‐blood samples for dried blood spot, Xpert HCV Viral Load and venepuncture samples. Participants underwent transient elastography and clinical assessment by a nurse or general practitioner. Among 839 participants (mean age 43 years), 66% were male (n = 550), 64% (n = 537) injected drugs in the previous month, and 67% (n = 560) reported currently receiving opioid substitution therapy. Overall, 45% (n = 380) had detectable HCV RNA, of whom 23% (n = 86) received HCV treatment within 12 months of enrolment. HCV treatment uptake increased from 2% in the pre‐DAA era to 38% in the DAA era. Significant liver fibrosis (F2‐F4) was more common in participants with HCV infection (38%) than those without (19%). Age 50 years or older (aOR, 2.88; 95% CI, 1.18‐7.04) and attending a clinical follow‐up with nurse (aOR, 3.19; 95% CI, 1.61‐6.32) or physician (aOR, 11.83; 95% CI, 4.89‐28.59) were associated with HCV treatment uptake. Recent injection drug use and unstable housing were not associated with HCV treatment uptake. HCV treatment uptake among PWID has increased markedly in the DAA era. Evaluation of innovative and simplified models of care is required to further enhance treatment uptake.